Quantifying the effects of anaerobic soil disinfestation and other biological soil management strategies on nitrous oxide emissions from raised bed plasticulture tomato production. Issue 2 (1st February 2022) - Li, Zhuona; Di Gioia, Francesco; Paudel, Bodh; Zhao, Xin; Hong, Jason; Pisani, Cristina; Rosskopf, Erin; Wilson, Patrick
Abstract: Soilborne pests are a major obstacle that must be overcome for the production of horticultural crops. Methyl bromide (MBr) was an effective preplanting soil broad‐spectrum biocide, but its use has been banned due to its role in depleting the ozone layer. As a result, sustainable alternative methods for controlling soilborne pathogens and pests are needed. Nitrous oxide (N2 O) emissions are of concern in crop production due to the role of N2 O as a greenhouse gas. Agricultural lands are known sources for emission of N2 O into the atmosphere. Emissions are related to many environmental factors as well as fertilization and fumigation practices. This study evaluated the influence of different alternatives to MBr on N2 O emissions throughout a tomato production season in two locations representative of southern and northern Florida. We evaluated eight soil management practices, including (a) untreated controls; (b) chemical soil fumigation; (c) anaerobic soil disinfestation using molasses (M) + composted poultry litter and (d and e) M + composted yard waste (CYW, at two rates); (f) Soil Symphony Amendment (SSA), a commercially available mix of microbes and nutrients; (g) CYW alone; and (h) CYW + SSA. Nitrous oxide emissions were measured throughout the cropping season. Emissions were highest on the day of planting (Day 21), ranging from 213 to 1, 878 μg m –2 h –1, likely due to the release of N2 O that had accumulated under the totally impermeable film when it was punctured for planting. However, statistical significance varied between sites. Estimated cumulative emissions of N2 O throughout the production season ranged from 1.3 to 4.8 kg N2 O–N ha –1 . Core Ideas: Emissions were highest on the day of planting (Day 21), ranging from 213 to 1, 878 μg m –2 h –1 . Average N2 O fluxes on Day 21 at planting were higher than those at other sampling times. Estimated cumulative emissions of N2 O throughout the production season ranged from 1.3 to 4.8 kg N2 O–N ha –1 .